A numerical investigation of the solid surface material influence on flow boiling within microchannels. (25th November 2022) - Vontas, Konstantinos; Miché, Nicolas; Marengo, Marco; Georgoulas, Anastasios
Highlights: The effect of solid surface thermophysical properties on flow boiling within microchannels is studied numerically. 3D transient simulations, accounting for conjugate heat-transfer effects, are performed. The study focuses on first transient stages of flow patterns development. Solid surface is playing an important role on the developing flow regimes and heat transfer coefficient. New correlation that accounts for thermal diffusivity effects is proposed. Abstract: Flow boiling within microchannel heat sinks constitute a promising solution for the cooling of high-performance electronic devices, dissipating high values of heat flux. Yet still, due to the complexity of flow boiling in small scales, the effect of important parameters is not clearly defined. In the present study a numerical investigation on the effect of solid surface thermophysical properties on flow boiling heat transfer characteristics within microchannels, is conducted. For the proposed investigation an enhanced, custom VOF-based numerical model that has been developed in OpenFOAM is used. The utilised computational domain consists of a top rectangular fluid domain in contact with a bottom rectangular solid domain. The solid domain is heated at its bottom boundary by the application of a constant heat flux. In total five different solid surface materials were examined, focusing on the first transient stages of the confined two-phase flow development. The findings indicate that the investigated effect has a significant influence on the resulting two-phase regimes and in the associated heat transfer characteristics. High thermal conductivity materials such as silver, aluminium and copper exhibited the highest values of the time-averaged heat transfer coefficient with more than 35% increase compared to the single-phase stage of the simulations, whereas the brass and silver channels resulted in a lower increase of<30%. The flow boiling process in the brass and silver channels, was characterised by frequent bubble break-ups and a lower total vapour fraction values within the channels. The rest of the examined material cases were characterised by thicker liquid films and higher values of total vapour fraction. Finally, a new correlation for the global Nusselt number is proposed that takes into consideration the thermophysical properties of the solid domain.